Analysis of Class II Intermaxillary Elastics Applied Forces: An in-vitro Study - Castroflorio, Tommaso; Sedran, Ambra; Spadaro, Francesca; Rossini, Gabriele; Cugliari, Giovanni; Quinzi, Vincenzo; Deregibus, Andrea (Frontiers in Dental Medicine, 2022)
Objectives The aims of this study were: (1) to assess the average inter-arch distances characterizing Class II malocclusions, (2) to analyze the applied forces at those distances by different elastics, and (3) to compare measured forces with those declared by manufacturers, both in dry and wet environments. Materials and Methods Settings and sample population: Class II models of 167 adult subjects (96 women and 71 men, age: 28 ± 3 years) referred to the Orthodontic Department of the University of Turin, Turin, Italy, between January 2018 and January 2020, were collected. Distances between facial axes (FA) points of upper canines and lower first molars (A), upper first premolar and lower first molar (B), upper second premolar and lower first molar (C), upper canine and lower first premolar (D), and upper canine and lower second premolar (E), were measured using 3Shape Ortho® Viewer program. Different elastics' diameters and forces were tested at those distances. The MTS Insight® Electromechanical Testing System was used to measure the tensile forces of elastics. The applied forces were measured in dry (T0) and wet conditions, after 1 (T1), 6 (T2), and 12 h (T3). Results Average distances were calculated: A = 24.64 mm (SD 2.10), B = 16.3 mm (SD 1.94), C = 9.78 mm (SD 1.77), D = 9.8 mm (SD 1.88), and E = 15.99 mm (SD 2.06). Significant differences (p < 0.05) were highlighted between the measured force and the force declared by manufacturers, and all elastics had a significant force decay (p < 0.05). Conclusion The results showed that 3/16" 4.5 oz are the most reliable elastics in terms of applied force with respect to the declared one and in terms of force degradation.